PERFORMAN LAJU PERTUMBUHAN RELATIF DAN KELULUSHIDUPAN UDANG VANNAME (Litopenaeus vannamei) MELALUI SUBSTITUSI TEPUNG IKAN DENGAN SILASE TEPUNG CACING TANAH (Lumbricus rubellus) - Diana Rachmawati; Istiyanto Samidjan (LPPM Universitas Pekalongan, 2015)
The objective of this study was to examine the effect of feeding substitution from fish meal to earthworm meal silage (Lumbricus rubellus) and also to determine the best dose of feeding substitution from fish meal to worm meal (Lumbricus rubellus) on relative growth rate and survival rate of Vanname Shrimp (Litopenaeus vannamei). Methodology used in this study was laboratory treatments with complete random design. The study consisted of four treatments and three repetitions. The treatments were feeding substitution from fish meal to worm meal with four different levels of mix; those were treatment A (0% of earthworm meal silage + 100% of fish meal), treatment B (25% of earthworm meal silage + 75% of fish meal), treatment C (50% of earthworm meal silage + 50% of fish meal), and treatment D (75% of earthworm meal silage + 25% of fish meal). The average weight of the Vanname shrimp used in this study ranged 1.7 ± 0.017 g/fish with stock density of 1 fish per liter. The artificial feed was in the form of pellet. Feeding time was three times a day. The results show that the substitution of feed ingredient from fish meal to earthworm meal silage significantly (P<0.01) affected on relative growth rate; however, it did not significantly (P>0.05) affect on survival rate of Vanname shrimp. The study also shows that the best level of feeding substituion from fish meal to earthworm meal silage was at the level of 25% (treatment B). The water quality during study was in viable range for the Vanname Shrimp (Litopenaeus vannamei) cultivation. Key words : Vanname shrimp, Substitution, Silage, Relative Growth, Survival Rate